CLINICAL AND FUNCTIONAL FEATURES OF THE COURSE OF BRONCHIAL ASTHMA WITH ALLERGIC RHINITIS IN CHILDREN - Abdullaev Сардорбек; Shamsiev Фуркат; Karimova Нилуфар (International Journal of Scientific Pediatrics, 2023)
Epidemiological studies of recent years have shown that in most patients, bronchial asthma (BA) and allergic rhinitis (AR) accompany each other, have common risk factors, similarity of the immunological response and chronic allergic inflammation. When BA is combined with AR, the disease is much more severe, and AR treatment reduces symptoms and alleviates the course of BA. Despite the evidence of the mutual negative influence of AR and BA, the factors contributing to their comorbidity are not fully understood. At present, it is not clear whether BA and AR are independent diseases or they represent different phenotypes of the same nosological unit; the reasons for the formation of these phenotypes have not been established, which determines the high relevance of studying the comorbidity of BA and AR in children. Purpose of the study. To study clinical, anamnestic and functional features of comorbidity of bronchial asthma and allergic rhinitis in children. Materials and research methods. We examined 69 patients with atopic BA without concomitant allergic diseases (group I) aged 3–16 years, and 77 patients with BA comorbid with allergic rhinitis (group II). The control group consisted of 20 practically healthy children of the same age. The study of the function of external respiration was carried out by the method of spirography in the department of pulmonology. Research results. The most frequent triggers of asthma exacerbation in history and at the time of the initial examination were acute respiratory diseases in children of the main groups. Changes in weather conditions are a well-recognized trigger for asthma exacerbations. It is believed that a possible mechanism for its implementation is an increase in the degree of atmospheric pollution with changing weather conditions. The connection of asthma attacks with emotional stress was noted in every fifth child of group I (14–20,29%) and every fourth (21–27,27%) of group II (p>0,05). Forced breathing spirometry is a highly informative method for diagnosing asthma and one of the main methods for monitoring the effectiveness of therapy, which makes it possible to carry out an individual prognosis of the course of the disease. In patients with BA of groups I and II, the average values ​​of FEV1 and the Tiffno index were predictably lower than those of healthy children, indicating the presence of broncho-obstructive syndrome. Comparison of spirometric indicators of children in groups I and II revealed statistically significant differences in VC. In patients of both groups, the average FVC is more than 80% of the VC, which is considered normal. In turn, the average VC index was significantly lower in patients of group I, and the Tiffno index did not differ significantly from the indicators of children in group II. Conclusions. In childhood, atopic bronchial asthma, comorbid with allergic rhinitis, is characterized by: the predominance of boys among all age groups of patients; development of early sensitization; the dependence of impaired respiratory function on contact with aeroallergens during the neonatal period; meteorological dependence of symptoms. Comparison of spirometric parameters revealed statistically significant differences in VC, which may be due not only to increased bronchial resistance, but also to reduced extensibility and elasticity of the lung tissue, i.e. decreased ability of the lungs to expand during inhalation.